A STUDY ON ACTIVITY POSITION ANALYSIS OF SELECTED INDIAN TEXTILE COMPANIES (International Journal of Food and Nutritional Sciences, 2022)
Activity ratios show how well a company uses its resources, including inventory, accounts receivable, and fixed assets. Activity ratios gauge how efficiently a business can use its asset, liability, and capital to create income in the form of cash and sales. Activity ratios are important in assessing a firm's operating efficiency since they not only show how efficiently a company makes revenue but also how well it is managed to make the most use of all of its balance sheet components. In this paper, activity position of some selected textile companies is closely monitored. In this process, excel and SPSS software is used to perform the analysis part. Thus, studying various statically parameters associated.